School Staff’s Viewpoints of Supervision: A Q-Methodological Study - Beech, Kirsty (2021)
Both the mental health and wellbeing of children and young people (CYP) (Department of Health (DoH) & Department for Education (DfE), 2017), and the wellbeing of school staff (DfE, 2019) are current government priorities, thus, the provision of supervision for school staff appears to be of increasing importance. Yet while supervision is compulsory for many professionals working with children and young people (CYP) it is largely uncommon in schools (Briggs, 2020). Indeed, the most recent Teacher Wellbeing Index (Education Support, 2020) found that only 8% of school staff surveyed currently accessed supervision. Barriers relating to terminology (Soni, 2019; Steel, 2001) and potential associated connotations (Kennedy & Laverick, 2019), suggest low uptake may be in part related to perceptions of supervision. Therefore, it seems that more needs to be understood about how school staff construe supervision. Q-methodology was utilised to explore the holistic viewpoints of school staff regarding supervision. Twenty one school staff working in a range of roles and settings, with varying experiences of supervision, completed an online Q-sort activity and a post-sort questionnaire. Two Viewpoints were identified within the sample. These were described as: 1. ‘Achievable and Necessary: Quality Supervision Benefits the Whole-School System’ 2. ‘Cautious Optimism: To be Successful Supervision Must be Clearly Defined, Embedded, Safe, Optional and Responsive’ Key implications of the research include reiterating the need to avoid a ‘one-size-fits’ all approach to supervision and the need to develop a shared understanding of supervision and a culture of supervision in schools. It is argued that the findings have potential implications for the Educational Psychologist (EP) role suggesting that EPs may be well placed to contribute at a systems level to facilitate access and engagement with supervision. The use of Q-methodology in answering the research question is discussed, strengths and limitations of the research are identified and suggestions for future research considered.